Implementation Of Enterprise Risk Management (ERM) In Analyzing Operational Risks In The Production Process: A Case Study Of UMKM Indogarment Pasir Honje Lamping - Dea Putri Andini; Keysa Utami (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze operational risks in the production process through the implementation of Enterprise Risk Management (ERM) at UMKM Indogarment Pasir Honje Lamping. The research adopts a quantitative approach with a case study method. Data were collected through direct observation, interviews, and the distribution of questionnaires to 25 employees involved in the production process. The research instrument consisted of a risk assessment questionnaire measuring probability (occurrence) and impact (severity), while data analysis was conducted using the ERM framework through risk scoring calculations and risk matrix mapping. The results indicate that 14 operational risks were identified and classified into five categories, namely human resource risk, process risk, system risk, raw material risk, and reputation risk. Based on the risk assessment, four risks were categorized as high risk, including delays in order completion, defective or damaged raw materials in roll form, embroidery or screen-printing errors, and production delays due to raw material shortages. This study is limited to operational risk analysis and does not examine financial impacts quantitatively, and it focuses on a single case study object. The findings are expected to provide practical contributions for garment sector MSMEs in managing operational risks and academic contributions to the development of risk management and operations management studies based on Enterprise Risk Management (ERM).